Suxamethonium induces a prompt increase in the bispectral index. Issue 16 (April 2017) - Choi, Jong Bum; Na, Se Hee; Lee, Sook Young; Kim, Jong Yeop; Park, Sung Yong; Kim, Ji Eun; Hong, Seungbae; An, Jiwon; Park, Chung Hoon; Kim, Yong Chan; Park, Woo Young
Abstract : Abstract: Upon inducting general anesthesia in the operating room, we have observed a prompt increase in the bispectral index (BIS) after the intravenous injection of suxamethonium. We hypothesized that the cause of this BIS increase is muscle hyperactivity owing to fasciculation. However, no reports have been published regarding this abrupt increase in the BIS upon the induction of general anesthesia by suxamethonium. To investigate the degree of change in the BIS in patients receiving anesthesia with suxamethonium, we performed a prospective observational study of 63 participants who underwent closed reduction for nasal bone fracture. Anesthesia was induced by the total intravenous administration of anesthetics and 1.5 mg kg −1 of suxamethonium was injected intravenously upon achieving BIS between 45 and 55. Intubation was performed after fasciculation. Electromyograms and BIS values were recorded from the induction of suxamethonium until 15 minutes after intubation. The mean BIS values were 95.4, 48.5, and 69.3 before induction, before the intravenous injection of suxamethonium, and immediately after fasciculation, respectively. The BIS value immediately after fasciculation (69.3 ± 10.6) was significantly higher than the cutoff BIS value of 60 ( P  < .001). Although fasciculation after the intravenous injection of suxamethonium resulted in the prompt increase of the BIS to values over 60, none of the participants was awake during surgery. In conclusion, the administration of suxamethonium resulted in the postfasciculation increase of the BIS to an average value of 69.3 without affecting the patient's state of consciousness.